Single-Cell Photothermal Analysis Induced by MoS2 Nanoparticles by Raman Spectroscopy - Rusciano, Giulia; Capaccio, Angela; Sasso, Antonio; Singh, Manjot; Valadan, Mohammadhassan; Dell’Aversana, Carmela; Altucci, Lucia; Altucci, Carlo (Frontiers in Bioengineering and Biotechnology, 2022)
Two-dimensional nanomaterials, such as MoS$_2$ nanosheets, are attracting an increasing attention in cancer diagnosis and treatment thanks to their peculiar physical and chemical properties. Although the mechanisms which regulate the interaction between these nanomaterials with cells are not yet completely understood, many studies have proved their efficient use in photothermal treatment of cancer. Less investigated is, instead, the response to MoS$_2$ nanosheets at single cell level. Clearly, this information can help in shedding light on the subtle cellular mechanisms ruling the interaction of this 2D material with cells and, eventually, to its cytotoxicity. In this study, we use confocal micro-Raman spectroscopy to reconstruct the thermal map of single cells targeted with MoS$_2$ under continuous laser irradiation. The experiment is performed by analyzing the water O-H stretching band around 3400 cm$^{-1}$ whose tetrahedral structure is sensitive to either molecular environment and temperature. Compared to fluorescence-based approaches, this Raman-based strategy for temperature measurement does not suffer from fluorophors instability, which can be significant under continuous laser irradiation. We demonstrate that irradiation of human breast cancer MCF7 cells targeted with MoS$_2$ nanosheets causes a relevant photothermal effect, which is particularly high in presence of MoS$_2$ nanosheets aggregates. The laser-induced heating is strongly localized near such particles which, in turn, tend to accumulate near the cytoplasmatic membrane. Globally, our experimental outcomes are expected to be important for tuning the nanosheets fabrication process.